Structural and Magnetic Properties of Silica-Coated Magnetite Nanoaggregates - Casagrande-Denardin, J (Elsevier B.V., 2019)
Magnetite nanoparticles were synthesized by the coprecipitation method. Additionally, two composites of silica-coated magnetite nanoparticles were synthesized by the Stöber method. The synthesized nanocompounds were characterized by X-ray diffraction, FTIR spectroscopy, transmission electron microscopy and vibrating sample magnetometry. The magnetite nanoparticles have a single crystalline phase corresponding to the cubic spinel structure. The magnetite nanocompound is formed by faceted nanoparticles with a mean size of 9 nm, while the composites consist mainly of aggregates of magnetite nanoparticles coated with silica, with mean sizes of 22 and 55 nm. The magnetization measurements of the three nanocompounds suggest that the nanoparticles are in the superparamagnetic regime at room temperature, with a small amount of nanoparticles in the blocked regime. © 2019 Elsevier B.V.